Optimasi Jenis Kertas untuk Strip Test Boraks dengan Indikator Crude Antosianin dari Ubi Jalar Ungu - Susanti, Siti; Bintoro, Valentinus Priyo; Bimonov, Salsabila Alya (Universitas Al Azhar Indonesia, 2024)
This research aims to determine the most optimal type of filter paper in making strip tests from crude anthocyanins of purple sweet potato to detect borax. The experimental design consisted of paper type optimization by testing magenta color intensity, sensitivity tests of strip tests using borax standard solution by testing cyan color intensity, and application of strip tests on food. Optimization of paper type was tested quantitatively with the treatment of ordinary filter paper and whatman paper number 1, 40, 41, and 42. The sensitivity was tested quantitatively with four concentrations of borax. The results of the application of borax test strip tests on food products were analyzed qualitatively. The results of the research on paper type optimization showed that the color intensity on 5 types of paper was significantly different, with the highest color intensity value owned by ordinary filter paper. Subsequent sensitivity tests on ordinary filter paper at four borax concentrations showed results with a detection limit of 1 ppm. The application test of purple sweet potato strip test, using ordinary filter paper, demonstrated its effectiveness as a borax detection tool in food products, with a sensitivity limit of up to 0.5%. The borax test strip paper produced in this research successfully detected the presence of borax in food products.Keywords – Anthocyanins, Borax, Filter Paper, Purple Sweet Potato.